AAV-mediated expression of NFAT decoy oligonucleotides protects from cardiac hypertrophy and heart failure - Remes, Anca; Wagner, Andreas H.; Schmiedel, Nesrin; Heckmann, Markus B.; Ruf, Theresa; Ding, Lin; Jungmann, Andreas; Senger, Frauke; Katus, Hugo; Ullrich, Nina D.; Frey, Norbert; Hecker, Markus; et al. (Basic research in cardiology, 2021)
Previous studies have underlined the substantial role of nuclear factor of activated T cells (NFAT) in hypertension-induced myocardial hypertrophy ultimately leading to heart failure. Here, we aimed at neutralizing four members of the NFAT family of transcription factors as a therapeutic strategy for myocardial hypertrophy transiting to heart failure through AAV-mediated cardiac expression of a RNA-based decoy oligonucleotide (dON) targeting NFATc1-c4. AAV-mediated dON expression markedly decreased endothelin-1 induced cardiomyocyte hypertrophy in vitro and resulted in efficient expression of these dONs in the heart of adult mice as evidenced by fluorescent in situ hybridization. Cardiomyocyte-specific dON expression both before and after induction of transverse aortic constriction protected mice from development of cardiac hypertrophy, cardiac remodeling, and heart failure. Singular systemic administration of AAVs enabling a cell-specific expression of dONs for selective neutralization of a given transcription factor may thus represent a novel and powerful therapeutic approach.